2014
DOI: 10.1021/bi4014566
|View full text |Cite
|
Sign up to set email alerts
|

Strong, Low-Barrier Hydrogen Bonds May Be Available to Enzymes

Abstract: The debate over the possible role of strong, low-barrier hydrogen bonds in stabilizing reaction intermediates at enzyme active sites has taken place in the absence of an awareness of the upper limits to the strengths of low-barrier hydrogen bonds involving amino acid side chains. Hydrogen bonds exhibit their maximal strengths in isolation, i.e., in the gas phase. In this work, we measured the ionic hydrogen bond strengths of three enzymatically relevant model systems in the gas phase using anion photoelectron … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
53
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(56 citation statements)
references
References 39 publications
2
53
1
Order By: Relevance
“…Further analysis of the energy hyperspace shows that the global minima of hydrogen bond energy do not coincide with the maximum populated bin. This observation is not unexpected as the macromolecules are much more biologically active (with many competing hydrogen bond interactions) compared to small molecules and the competition to form a hydrogen bond in solution is also immense in number, thus lowering the average strength of the hydrogen bond per pair . Comparative analysis of peptide–PES and protein–PES also shows that for peptides the global minima and maximum populated bin lies much closer than that of proteins, in accordance with the later study.…”
Section: Discussionsupporting
confidence: 84%
“…Further analysis of the energy hyperspace shows that the global minima of hydrogen bond energy do not coincide with the maximum populated bin. This observation is not unexpected as the macromolecules are much more biologically active (with many competing hydrogen bond interactions) compared to small molecules and the competition to form a hydrogen bond in solution is also immense in number, thus lowering the average strength of the hydrogen bond per pair . Comparative analysis of peptide–PES and protein–PES also shows that for peptides the global minima and maximum populated bin lies much closer than that of proteins, in accordance with the later study.…”
Section: Discussionsupporting
confidence: 84%
“…It has long been hypothesized but also a matter of debate that LBHBs can supply up to 10–20 kcal/mol of free energy for enzymatic reactions, significantly higher than approximately 3–5 kcal/mol for a standard HB 1,4 . A recent study has suggested that LBHBs can play a special role in enzyme catalysis to the extent the semi-solid and weakly-polar character of an enzyme active site can support a LBHB with a reasonable fraction of the strengths found in the gas phase 3 . The existence of such LBHBs in proteins however, has been subject to intense debate, partly due to the lack of direct observation by X-ray crystallography 37,38 .…”
Section: Resultsmentioning
confidence: 99%
“…There have been numerous discussions of possible alterations in the energetic properties of catalytic interactions from creation of an active site environment that differs from and is sequestered from aqueous solution (Berg et al, 2002;Cleland and Kreevoy, 1994;Dewar and Storch, 1985;Gerlt and Gassman, 1993;Graham et al, 2014;Richard et al, 2014;Shan and Herschlag, 1999;Warshel, 1998;Warshel et al, 2006). However, prior studies have shown that the dependence of catalysis and TSA binding on the charge densities of the oxyanion and the oxyanion hole hydrogen bond donors is similarly shallow to hydrogen bond dependencies observed in aqueous solution; the stronger dependencies observed in non-aqueous environments such as organic solvents and the gas phase are not observed within the KSI oxyanion hole (Kraut et al, 2006;Natarajan et al, 2014;Peter Guthrie, 1996;Sigala et al, 2015).…”
Section: Summary Of Ksi Catalytic Implicationsmentioning
confidence: 99%